2MDR, a microcomputer-controlled visual stimulation device for psychotherapy-like treatments of mice - Jauch, Isa; Kamm, Jan; Benn, Luca; Rettig, Lukas; Friederich, Hans-Christoph; Tesarz, Jonas; Kuner, Thomas; Wieland, Sebastian (eNeuro, 2023)
Post-traumatic stress disorder and other mental disorders can be treated by an established psychotherapy called Eye Movement Desensitization and Reprocessing (EMDR). In EMDR, patients are confronted with traumatic memories while they are stimulated with alternating bilateral stimuli (ABS). How ABS affects the brain and whether ABS could be adapted to different patients or mental disorders is unknown. Interestingly, ABS reduced conditioned fear in mice. Yet, an approach to systematically test complex visual stimuli and compare respective differences in emotional processing based on semiautomated/automated behavioral analysis is lacking. We developed 2MDR (MultiModal Visual Stimulation to Desensitize Rodents), a novel, open-source, low-cost, customizable device that can be integrated in and transistor-transistor logic (TTL) controlled by commercial rodent behavioral setups. 2MDR allows the design and precise steering of multimodal visual stimuli in the head direction of freely moving mice. Optimized videography allows semiautomatic analysis of rodent behavior during visual stimulation. Detailed building, integration, and treatment instructions along with open-source software provide easy access for inexperienced users. Using 2MDR, we confirmed that EMDR-like ABS persistently improves fear extinction in mice and showed for the first time that ABS-mediated anxiolytic effects strongly depend on physical stimulus properties such as ABS brightness. 2MDR not only enables researchers to interfere with mouse behavior in an EMDR-like setting, but also demonstrates that visual stimuli can be used as a noninvasive brain stimulation to differentially alter emotional processing in mice.